PENGARUH EFIKASI DIRI DAN LINGKUNGAN TERHADAP NIAT BERWIRAUSAHA MAHASISWA (STUDI PADA MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS TARUMANAGARA) - Hendra Wiyanto (Jurnal Manajemen., 2014)
This study was conducted to examine the effect of self-efficacy and environmental on entrepreneurial intention of student. This study uses a quantitative approach. Samples taken in this study were 50 students of Management Department Faculty of Economics Universitas Tarumanagara with purposive sampling method with sample criteria that students are following courses of entrepreneurship specialization. Analytical technique used in this study is multiple regression. The study findings showed that (1) self-efficacy and the environment together significantly influence entrepreneurial intention of students (2) self-efficacy partially significant effect on entrepreneurial intention in college students (3) Environment partially significant effect on the intention entrepreneurship in students. The finding of the research implicates that what has been indicated by a theory that predicts self-efficacy and environmental that is assumed to affect the interest to make business through entrepreneurial intention prevail for the area student of Management study program, Economic faculty Universitas Tarumanagara. Based on the result of the research, self-efficacy that is a part of output of entrepreneurship course affects directly and positively to the interest to make business. The result of the research also consolidates the previous research that had tested the direct effect of self-efficacy towards interest. Based on findings of this study, it can be suggested that efforts to foster student interest in entrepreneurship can be done by improving self-efficacy. For this to happen it is necessary to design the curriculum of entrepreneurship courses that can shape and improve the self-efficacy of students as this will have an impact on increasing student interest in opening a business.